Alternate nonmagnetic and magnetic multilayer nanofilms deposited on carbon nanocoils by atomic layer deposition to tune microwave absorption property. (March 2016) - Zhao, Shichao; Gao, Zhe; Chen, Chaoqiu; Wang, Guizhen; Zhang, Bin; Chen, Yao; Zhang, Jing; Li, Xiao; Qin, Yong
Abstract: In this study, alternate nonmagnetic Al2 O3 and magnetic Fe3 O4 multilayer nanofilms with precisely controlled thickness were deposited on carbon nanocoils by atomic layer deposition. The as-synthesized composites exhibit superior microwave absorption performance, which can be flexibly tuned by varying the thickness of each individual layer or the number of layers. The excellent absorption performance arises from the effective impedance matching, alternate multilayer nanostructure and chiral morphology of the samples, and efficient magnetic loss from magnetic constituents. Our work demonstrates a new strategy to tune microwave absorption performance and this method can be extended to exploit other excellent microwave absorbers with alternate multilayer hetero-nanostructures owing to the convenient control of electromagnetic parameters.